2022
DOI: 10.1159/000525050
|View full text |Cite
|
Sign up to set email alerts
|

miR-181a Improved Renal Inflammation by Targeting TNF-α in a Diabetic Nephropathy Animal Model

Abstract: <b><i>Introduction:</i></b> Recent studies have elucidated that miR-181a plays a vital role in various inflammation-associated diseases; however, its role in the pathogenesis of diabetic nephropathy (DN) has not been elucidated clearly. Hence, we investigated the involvement of miR-181a in the pathogenesis of DN in patients and animal models. <b><i>Methods:</i></b> miR-181a levels were measured in the kidneys of DN patients and a DN mouse model (db/db mice) by RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, further investigation is needed to explore the correlation between miR-192 derived from EVs and other renal function indicators. Other studies showed that urinary EV miR-181a was significant reduced in CKD patients at all stages, as well as in DN patients ( Khurana et al, 2017 ; Zha et al, 2019 ; Liu et al, 2022 ). Furthermore, miR-181a overexpression could reduce glomerulosclerosis and tubular epithelial injury ( Liu et al, 2018d ).…”
Section: Evs As Biomarkers Of Chronic Kidney Diseasementioning
confidence: 86%
“…However, further investigation is needed to explore the correlation between miR-192 derived from EVs and other renal function indicators. Other studies showed that urinary EV miR-181a was significant reduced in CKD patients at all stages, as well as in DN patients ( Khurana et al, 2017 ; Zha et al, 2019 ; Liu et al, 2022 ). Furthermore, miR-181a overexpression could reduce glomerulosclerosis and tubular epithelial injury ( Liu et al, 2018d ).…”
Section: Evs As Biomarkers Of Chronic Kidney Diseasementioning
confidence: 86%
“…miR-181a overexpression in mesangial cells reduces IL-6 and IL-1β levels, attenuating DN-associated inflammation. 22 In vitro models simulating DN suggest that increased miR-485 expression mitigates inflammation and limits mesangial cell proliferation. Recent research has suggested that miR-141 suppresses DN partly through its inhibitory impact on ICAM-1, with empirical support from feedback verification studies.…”
Section: Significance Statementmentioning
confidence: 99%
“…The miRNA miR‐141, in particular, has been noted for its ability to inhibit ICAM‐1 and thereby exert a protective effect against DN. miR‐181a overexpression in mesangial cells reduces IL‐6 and IL‐1β levels, attenuating DN‐associated inflammation 22 . In vitro models simulating DN suggest that increased miR‐485 expression mitigates inflammation and limits mesangial cell proliferation.…”
Section: Icam‐1 and Diabetic Nephropathymentioning
confidence: 99%
“…miR-149 shows its anti-inflammatory response via targeting TAK1/NF-ĸB signaling in osteoarthritic chondrocytes [ 80 ]. miR-181a down-regulates TNF-α, thereby improving renal inflammation in the diabetic nephropathy animal model [ 81 ]. The down-regulation of miR-150 induces the LPS-mediated release of pro-inflammatory cytokines in THP-1 macrophages via STAT1 up-regulation [ 82 ].…”
Section: Anti-inflammatory Mirnasmentioning
confidence: 99%